Features of Somatic and Reproductive Status of Women, who Gave Birth to a Child with Congenital Malformations, and Their Identifiсation Using «Case - Control» Method According to Data of Lviv Regional Clinical Perinatal Center in 2007-2009 - Zborovska N.V. Zborovska N.V; Lukyanenko N.S. Lukyanenko N.S; Kitsera N.I. Kitsera N.I (Zaslavsky O.Yu., 2012)
There were carried out collection and analysis of clinicoepidemiological and medical-statistic data from 162 sources of primary documentation (childbirth history (096/o form) and the development of newborns (097/o form)) about children with congenital malformations, who were born in Lviv Regional Clinical Perinatal Center in 2007-2009, using «case - control» method, by filling-in registration forms. While comparing a range of reproductive anamnesis indices there was noticed a higher percentage of dead children, stillbirths, anemia in pregnancy, gestosis in the first half of pregnancy, gestosis in the second half of pregnancy, abnormal labors in mothers who gave birth to a child with congenital malformations than in women of control group. According to ultrasound diagnosis congenital abnormalities in pregnancy were detected in 31.6 % of cases. There were diagnosed 4 cases of Arnold - Chiari syndrome (spina bifida and internal hydrocephalus); and 3 cases of each: hydrocephalus, gastroschisis, small intestinal atresia, and 2 cases of each: congenital malformations, hypoplastic left heart syndrome, Down's syndrome, congenital diaphragmatic hernia, omphalocele, congenital rectal atresia, and 1 case of each: spina bifida, congenital absence of forearm and hand, left ventricular rabdomioma, encephalocele.